Alpha-synuclein is present in dental calculus but not altered in Parkinson's disease patients in comparison to controls - Schmid, Sabrina Franziska; Goldberg-Bockhorn, Eva; Schwarz, Silke; Rotter, Nicole; Kassubek, Jan Rainer; Del Tredici, Kelly; Pinkhardt, Elmar Hans; Otto, Markus; Ludolph, Albert C.; Oeckl, Patrick (Journal of neurology, 2018)
INTRODUCTION: In autopsy cases staged for sporadic Parkinson's disease (PD), the neuropathology is characterized by a preclinical phase that targets the enteric nervous system of the gastrointestinal tract (GIT). Therefore, the ENS might be a source of potential (presymptomatic) PD biomarkers. - METHODS: In this clinically based study, we examined the alpha-synuclein (αSyn) concentration in an easily accessible protein storage medium of the GIT, dental calculus, in 21/50 patients with PD and 28/50 age- and gender-matched controls using ELISA. - RESULTS: αSyn was detectable in dental calculus and the median concentration in the control patients was 8.6 pg/mg calculus (interquartile range 2.6-13.1 pg/mg). αSyn concentrations were significantly influenced by blood contamination and samples with a hemoglobin concentration of > 4000 ng/mL were excluded. There was no significant difference of αSyn concentrations in the dental calculus of PD patients (5.76 pg/mg, interquartile range 2.91-9.74 pg/mg) compared to those in controls (p = 0.40). - CONCLUSION: The total αSyn concentration in dental calculus is not a suitable biomarker for sporadic PD. Disease-related variants such as oligomeric or phosphorylated αSyn in calculus might prove to be more specific.
Published: 29 March 2018
Gesehen am 26.03.2020